Penerapan Strategi Pemasaran Digital dengan Menggunakan Sosial Media pada Kedai Kopi Windsor Central - Johny Budiman; Rudiyanto (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Windsor Central Coffee Shop is a Micro, Small and Medium Enterprise (MSME) in Batam City which was founded in 2003 and is managed directly by Mrs. Kha Tiang with 3 employees. During its 20 years of operation, this MSME does not have a food menu or digital marketing. The aim of this activity is to help the Windsor Central Coffee Shop develop a digital marketing strategy and create a food menu in QR Code form. The results of this activity provide significant changes compared to before the implementation activity, this is evidenced by Instagram and Facebook insight data, the number of consumers who sent messages on WhatsApp Business, and reviews from consumers regarding the implementation of the QR Code for food menus.